2014
DOI: 10.5513/jcea01/15.1.1412
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of the Pigs Housed in Hot Climatic Conditions

Abstract: The effect of high temperature on the behaviour of growing-finishing pigs was studied. The pigs were housed in a climate controlled chamber, the air temperature was kept constant at 30°C and the relative humidity was 32.5% during the whole 3 months. Aggressive behaviour and daily activities of the pigs were recorded during the light hours, from 6:00 till 18:00. Detailed observations showed that during the experiment, the pigs were most of the time lying (72%, P<0.001). Pigs spent more time lying on the floor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Nonetheless, these results are consistent with those of Amaral et al (2014), who observed a variation of 1.71% to 2.75% for seated animals. Even lower values were reported by Debreceni et al (2014), who observed the pattern "sitting" in 1% of the observations. Guy et al (2002) did find a difference between the evaluated systems.…”
Section: Behaviormentioning
confidence: 58%
See 3 more Smart Citations
“…Nonetheless, these results are consistent with those of Amaral et al (2014), who observed a variation of 1.71% to 2.75% for seated animals. Even lower values were reported by Debreceni et al (2014), who observed the pattern "sitting" in 1% of the observations. Guy et al (2002) did find a difference between the evaluated systems.…”
Section: Behaviormentioning
confidence: 58%
“…Pigs housed in the concrete floor system (11.19%) showed higher frequencies than those housed in the deep bedding systems (< 8%) for the behavior pattern "eating." According to the results of Debreceni et al (2014), the "eating" behavior was observed at an average frequency of 16%. This value is corroborated by Amaral et al (2014), who observed frequencies around 15.48%-18.75% during daytime.…”
Section: Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results of Debreceni et al (2014), normal eating behavior has an average frequency of 16%. This value is slightly higher than the frequencies observed in the present study, which was 13.33% in both pens.…”
Section: Resultsmentioning
confidence: 99%